Pembelajaran BIPA Berbasis Audiovisual: Memperkenalkan Pakaian Adat Sumatera kepada Siswa Sekolah Dasar. - Sari, Widya Arfiyantii Puspa; Syahfitri, Dian; Karina, Agita; Rajagukguk, Sadar M.; Sihombing, Tuty Susianti (Universitas Harapan Medan, 2025)
Effective Indonesian Language for Foreign Speakers (BIPA) instruction for elementary school children can be enhanced through the use of engaging audiovisual media relevant to Indonesian culture. This study presents an audiovisual-based BIPA learning model focused on introducing traditional clothing from provinces in Sumatera. The research employs a qualitative descriptive approach and is designed as a creative teaching concept rather than empirical research. In this approach, upper elementary students (ages 11-12 level A2) are shown audiovisual content featuring traditional clothing, followed by a picture-guessing activity to identify the displayed attire. After that, the students present the philosophical meaning of the traditional clothing. This strategy aims to make it easier for beginning BIPA learners to understand and retain new vocabulary related to Indonesian culture, particularly Sumatera. The use of audiovisual media is expected to increase student interest, while the picture-guessing activity reinforces memory and comprehension of the material. This culture-based learning approach is also anticipated to be engaging and contextual, aligning with the communicative and meaningful language learning needs of young learners. Keywords: BIPA, audivisual media, traditional clothing, Sumatera island, elementary school